2022
DOI: 10.3390/cancers14071721
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 (CA27.29) before and after Chemotherapy and Prognosis in High-Risk Early Breast Cancer Patients

Abstract: Soluble MUC1 has been discussed as a biomarker for predicting prognosis, treatment efficacy, and monitoring disease activity in breast cancer (BC) patients. Most studies in adjuvant settings have used preoperative assessment. This study, part of the SUCCESS-A trial (NCT02181101), assessed the prognostic value of soluble MUC1 before and after standard adjuvant chemotherapy. Patients with high-risk BC were treated within the SUCCESS-A trial with either three cycles of 5-fluorouracil, epirubicin, and cyclophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…The biochemical diagnosis of breast cancer has mostly supportive applications and generally uses cancer antigen 15-3 (CA 15-3), cancer-embryonic antigen (CEA), and cancer antigen 27.29 (CA 27.29) [ 15 , 16 , 17 , 18 ]. However, the previously mentioned low sensitivity and specificity of these compounds preclude their use in screening [ 19 , 20 ].…”
Section: Breast Cancer: a Brief Overviewmentioning
confidence: 99%
“…The biochemical diagnosis of breast cancer has mostly supportive applications and generally uses cancer antigen 15-3 (CA 15-3), cancer-embryonic antigen (CEA), and cancer antigen 27.29 (CA 27.29) [ 15 , 16 , 17 , 18 ]. However, the previously mentioned low sensitivity and specificity of these compounds preclude their use in screening [ 19 , 20 ].…”
Section: Breast Cancer: a Brief Overviewmentioning
confidence: 99%
“…It can also be assumed in further follow-up that an indication for active disease can be beneficial. With tumour markers and circulating tumour cells, it has already been shown that even 2 years after the primary diagnosis, a further classification into prognostic groups is possible [62,63].…”
Section: Analysis Of Ctdna Not Yet Clinical Routine In Patients With ...mentioning
confidence: 99%
“…Auch in der weiteren Nachsorge kann davon ausgegangen werden, dass eine Indikation für eine aktive Erkrankung von Nutzen sein kann. Mit Tumormarkern und zirkulierenden Tumorzellen ist bereits gezeigt worden, dass auch 2 Jahre nach der Primärdiagnose eine weitere Einteilung in prognostische Gruppen möglich ist [62,63].…”
Section: Molecular Diagnosticsunclassified
“…Mucin 1 (MUC1) is a transmembrane protein specifically and highly expressed in various BC tissues. 11 13 MUC1 plays a crucial role in the development and prognosis of BC, 14 making it an important target for imaging and therapeutic interventions in BC. 15 Nucleic acid aptamers (Apts) are short oligonucleotide fragments, including single-stranded DNA or small molecule RNA, which have shown great potential for targeted diagnosis and treatment of tumors.…”
Section: Introductionmentioning
confidence: 99%